Desenvolvimento de uma nova metodologia estabelecendo cotas para a evolução de trincas para modelos de carregamento com amplitude de tensão constante - Santos, Rodrigo Villaca (2015)
Most machines and mechanical components are subject to dynamic loads that can lead to fatigue failures. One of the methods for the prediction of fatigue failures is the Linear Elastic Fracture Mechanics (LEFM). In the LEFM there are several models that describe the propagation of a crack, with their different approaches and conceptions. In general, a distinction is made between the crack propagation models under constant and variable amplitude load. One of the constant amplitude load models is the Paris law, consisting of an Initial Value Problem (IVP), whose solution, in a few cases, can be obtained in closed form. Thus, the objective of this work is to propose a new methodology to solve some models of crack propagation under constant amplitude load, as the models of Paris-Erdogan, Forman, Walker, McEvily and Priddle, without requiring the use of numerical methods for the solution. This methodology was developed by establishing upper and lower bounds that delimit the behavior of the solutions of the models of crack propagation. For that, through literature, were delimited the models to be assessed on the basis of two main aspects: models that incorporate in their equations the regions I to III of the crack propagation, and models that take into account parameters such as the stress ratio, fracture toughness and threshold stress intensity factor for crack propagation. For verification of the accuracy and effectiveness of the new methodology, the relative deviation between bounds and approximate numerical solution was calculated, using the Runge-Kutta 4th order (RK4), and it was observed that the bounds are valid as a way of obtaining approximate solutions to all models. The performance of the use of bounds regarding the RK4 method solution was also evaluated through the computation time.